Sistem Monitoring dan Kontrol Motor AC 3 Phasa Melalui Inverter dengan Protokol Modbus Menggunakan Visual Basic Berbasis Atmega 2560 - Emillia Kartika; Ta'ali Ta'ali; Hastuti Hastuti (Universitas Negeri Padang, 2020)
A three-phase induction motor is one of the electric machines and is classified as an AC motor that is widely used in the industrial world. The development of control systems in the industry will not be separated from the data communication system. To send data from the field (sensor) to the controller, for communication between controllers, to send data from the controller to the computer, all require data communication. One of the most widely used data communication systems in industrial control systems is the Modbus protocol. Even in the world of education there are also many studies that develop control systems using modbus communication. The speed regulation of three phase induction motor can be done in various ways one of them is by using Variable Speed Drive which functions to adjust the frequency of the source so as to get the desired motor speed (rpm). Communication between VSD, Arduino and PC with the MODBUS protocol is a system built to be able to monitor the performance of a three phase induction motor.